2(4x+6)=-26+6

Simple and best practice solution for 2(4x+6)=-26+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(4x+6)=-26+6 equation:



2(4x+6)=-26+6
We move all terms to the left:
2(4x+6)-(-26+6)=0
We add all the numbers together, and all the variables
2(4x+6)-(-20)=0
We add all the numbers together, and all the variables
2(4x+6)+20=0
We multiply parentheses
8x+12+20=0
We add all the numbers together, and all the variables
8x+32=0
We move all terms containing x to the left, all other terms to the right
8x=-32
x=-32/8
x=-4

See similar equations:

| 26=-6b | | 4(-2+4x)+5=-25-6x | | n/5+-28=-38 | | 5(7x+6)=135 | | 6+4x=-3+8-2x=7x | | 15+3x=30 | | 32+8x=56 | | 790=-33y | | 2(4x+6)=-26=6 | | -5+3x=3-x | | 9n+24n+45=180 | | -7.6=x/4-1.2 | | (7x+5)=(5x+19) | | 14+2x=28 | | 15x–30–10x=15 | | (6x-5)×(2x+5)+(4x-5)×(1-3x)=48 | | 0.5(7d+4)=7.5d | | .50+1.5x+10=15 | | 4x-27=x+21 | | 5y+30=-2(y-1) | | 10+7x-3x=3-3x | | q+60=-29 | | 45b-8/30-20=10 | | ½(4l-6)=3l+6 | | 2(3x+9)=-46+28 | | 2x/5-7=9 | | -1+5(d-2)=12d+3-7d | | 25=w/4=17 | | 7(z-2)=296+6z | | 47+5x=87 | | 3c^2+13c-30=0 | | 1+x+2+3x=-9 |

Equations solver categories